Acid-etched Fe/Fe2O3 nanoparticles encapsulated into carbon cloth as a novel voltammetric sensor for the simultaneous detection of Cd2+ and Pb2. Issue 2 (19th November 2020) - Zhu, Fudan; Shi, Huilan; Yu, Zhe; Wang, Cunli; Cheng, Wenjing; Zhou, Xian; Yang, Fengchun; Zhang, Yuxi; Zhang, Xin
Abstract : A portable electrode with usability, availability, and high-sensitivity is of great significance for effective on-site detection in practical situations. Abstract : A portable electrode with usability, availability, and high-sensitivity is of great significance for effective on-site detection in practical situations. In this paper, a novel flexible, disposable sensor for Cd 2+ and Pb 2+ with ultrahigh sensitivity and a fast response, based on acid-etched Fe/Fe2 O3 encapsulated into a disposable carbon cloth electrode, has been successfully fabricated. Differential pulse anode stripping voltammetry (DPASV) was used to investigate the stripping behavior of Cd 2+ and Pb 2+, achieving high sensitivity for Cd 2+ and Pb 2+ (338.7 and 408.0 μA mM −1 cm −2 ) with limits of detection (LODs) of 0.42 ppb and 0.50 ppb, respectively. Meanwhile, remarkable stability and reproducibility were obtained. Such an electrode can detect Cd 2+ and Pb 2+ in actual water samples so this is a good candidate to act as a simple and convenient sensor for general applications. More importantly, the novel disposable electrode exhibited the unique advantages of convenience, portability, and reliability compared to a conventional electrode, which may make it an alternative advantageous choice for practical on-site detection.